Self-adaptive stepsize affine projection based parameter estimation of IPMSM using square-wave current injection - Gaolin Wang; Chen Li; Guoqiang Zhang; Dianguo Xu (CES Transactions on Electrical Machines and Systems, 2017)
Affine projection algorithm (APA) has been used to estimate the parameters of interior permanent magnet synchronous motor (IPMSM). However, there is not a strict guideline of choosing the stepsize of this algorithm to make sure that the results of parameter estimation are convergent. In order to solve such problem, self-adaptive stepsize affine projection algorithm for parameter estimation of IPMSM is proposed in this paper. Compared with traditional affine projection algorithm, this method can obtain the stepsize automatically based on the operation condition, which can ensure the convergence and celerity of the process of parameter estimation. Then, on the basis of self-adaptive stepsize affine projection algorithm, a novel parameter estimation method based on square-wave current injection is proposed. By this method, the error of estimated parameter caused by stator resistance, linkage magnetic flux and dead-time voltage can be reduced effectively. Finally, the proposed parameter estimation method is verified by experiments on a 2.2-kW IPMSM drive platform.